Cluster analysis in lipid biomarker studies: a case of the clyde sea - Masni Mohd Ali; Stephen M. Mudge (Universiti Kebangsaan Malaysia, 2006)
Thirty-three surface sediment samples were collected around the Clyde Sea and were analyzed for fatty acids, fatty alcohols and sterols by the GC-MS detection. Cluster analysis (Ward’s method with correlation coefficient) performed separately on fatty acids, fatty alcohols and sterols showed that they were grouped according to their geochemical sources. However, terrestrial derived compounds can be seen grouping with marine and bacterial derived compounds in every analysis. Bacterial derived compounds can be found in all clusters in the mixed compound cluster analysis showing that bacterial inputs occurred together with marine and terrestrial inputs.